2016
DOI: 10.1007/s11064-015-1811-y
|View full text |Cite
|
Sign up to set email alerts
|

Harpagophytum Procumbens Ethyl Acetate Fraction Reduces Fluphenazine-Induced Vacuous Chewing Movements and Oxidative Stress in Rat Brain

Abstract: Long-term treatment with fluphenazine is associated with manifestation of extrapyramidal side effects, such as tardive dyskinesia. The molecular mechanisms related to the pathophysiology of TD remain unclear, and several hypotheses, including a role for oxidative stress, have been proposed. Harpagophytum procumbens is an herbal medicine used mainly due to anti-inflammatory effects, but it also exhibits antioxidant effects. We investigated the effect of ethyl acetate fraction of H. procumbens (EAF HP) in fluphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…Recently, our group showed that treatment with Harpagophytum procumbens, a plant known for its anti-inflammatory properties, reduced the number of VCMs induced by fluphenazine in rats [70], once again suggesting that the development and progression of these motor disorders may be linked with inflammation at CNS.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, our group showed that treatment with Harpagophytum procumbens, a plant known for its anti-inflammatory properties, reduced the number of VCMs induced by fluphenazine in rats [70], once again suggesting that the development and progression of these motor disorders may be linked with inflammation at CNS.…”
Section: Resultsmentioning
confidence: 96%
“…This results in an early and sharp increase in membrane oxidative injury. Actually, the observed inhibitory effects on MDA production could be related to the radical scavenging activities of Harpagophytum (Grant et al , ; Schaffer et al , ). In addition, we observed an inhibitory effect induced by Harpagophytum extract on 3‐HK level, a marker of neurotoxicity synthesized by kynurenine monooxygenase (KMO) which generates free radicals in the brain (Maddison and Giorgini, ).…”
Section: Resultsmentioning
confidence: 99%
“…The same authors also observed a direct scavenging activity. On the other hand, Harpagophytum extract (ethyl acetate fraction) treatment could also stimulate catalase activity, a well‐established anti‐oxidative marker (Schaffer et al , ). 5‐HT pro‐inflammatory role in IBDs has been previously suggested (Regmi et al , ), possibly involving the activation of 5‐HT3 receptors (Mousavizadeh et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the traditional use is consistent, albeit in part, with the down-regulation of multiple pathways involved in inflammation, including ROS, cytokines and prostaglandin production (Huang et al, 2006;Grant et al, 2009;Fiebich et al, 2012;Schaffer et al, 2013;Schaffer et al, 2016Günther et al, 2006. On the other hand, the possible hepatic cytotoxic effects induced by Harpagophytum and harpagoside should be taken in consideration (Biazi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%